DEVELOPMENT OF MIDDLE/MTS MATHEMATICS LEARNING MEDIA BASED ON ISLAMIC COMMUNITY CULTURE ACEH BESAR - Marna Aina; Novi Trina Sari (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2021)
ABSTRACKThe presence of ethno-mathematics in mathematics learning provides a new nuance that learning mathematics is not only confined in the classroom but the outside world by visiting or interacting with local culture can be used as a medium for learning mathematics. The research begins with the activity of exploring and examining the potential for the use of religious and cultural sites (artifacts) as learning media for various mathematics teaching materials at the junior high school level using a qualitative approach followed by research and development (RD) methods following the 4D model at the product trial stage. The stages taken are the define stage, the planning stage, the develop stage and the dissemination stage. Data collection techniques in this study were interviews and questionnaires. Validation is carried out by material experts. Based on the results of the validation of the quality stage of the learning media content, it was obtained an average score of 89.46% with the criteria